Paciente femenino de 38 años de edad con obesidad mórbida grado iii e hipercolesterolemia. - Arana Muñoz, Noemi Lilibeth (2018)
Obesity is a health problem of the first magnitude, it is associated with greater global morbidity and mortality, and several factors such as cardiovascular risk. The causes of overweight and obesity are based on an energy imbalance between calories consumed and spent, People with obesity are more likely to suffer from hypercholesterolemia. In the present case, it is necessary to improve the nutritional status of the patient and establish her diagnosis, as well as perform nutritional intervention as an essential part of the treatment accompanied by monitoring and monitoring. Through the diagnosis established through the clinical, anthropometric, dietary and biochemical methods, we proceeded to perform the nutritional intervention: a diet of 1603 Kcal / day - low fat, and high in insoluble fiber and a distribution of macronutrients; carbohydrates 60%, protein 15% and fats 25%, a fractionation of 3 main meals and 2 snacks. The prescribed treatment will help improve the nutritional status of the patient.